Pendidikan Kewarganegaraan Berbasis Multikultural di Mts. Al Hamid Banjarmasin - triyono, sigit (Transformatif, 2017)
This study used a qualitative approach naturalistic sociometry test, the subject of research is the principal, vice-principal areas of curriculum / student, students in the academic year 2015/2016, for the principal one person, the vice principal curriculum areas 1, vice-principals student field 1, while for learners 30 people. Data collection techniques gained through observation, interviews, documentation, test sosiomentri and literature. The results of this study to prepare schools in addressing the differences among them are the principal called a meeting to the board of teachers and their vice principal of student and curriculum to discuss the creation of lesson plans which include a plan of material to be taught and the objectives to be achieved, while the curriculum used by the MTs Al Hamid Banjarmasin ie curriculum SBC Plus, learning to use the curriculum in English. The role of the vice principal of student field of multicultural education in assisting the implementation of directly applied in the form of extracurricular activities. Evaluation of multicultural education in MTs Al Hamid Banjarmasin has been successfully implementing the learning process of multicultural education. This is evident in the daily Siswan and teachers despite its students come from different social strata, but can get along and respect each other regardless of differences.Keywords: Planning, Implementation, Evaluation, Multicultural Education and Civics.Â